THE FORMULATION OF TEXTURED VEGETABLE PROTEIN AND GREEN BEEN FLOUR (Vigna radiata L.) IN MAKING ANALOGUE MEATBALLS - Satiah Satiah; Maherawati Maherawati; Tri Rahayu (Universitas Muhammadiyah Mataram, 2020)
Analog meatballs are one of the vegetarian products made using vegetable ingredients as a source of protein. Vegetable ingredients that can be used as a source of protein are textured vegetable protein and green beans. The aim of this research was to determine the formulation of textured vegetable protein and green bean flour that produced the best physical, chemical and sensory characteristics of analog meatballs. The research using Randomized Blok Design of one factor (formulation of textured vegetable protein and green bean flour) with six level of treatments (0:0, 35:40, 30:45, 25:50, 20:55, 15:60) and 4 replications. Data were analyzed using ANOVA (α = 5%) and if there was an significant different followed by BNJ test (α = 5%). The results showed that the best formulation based on effective index test of textured vegetable protein:green bean flour (30:45) that has moisture content of 56.77%; protein 10.89%; crude fiber of 0.73%; water holding capacity of 50.00%; elasticity level 4.47 Kg force; color 3.92 (slightly pale to near dark); 2.52 aroma (unpleasant); 2.64 flavor (tasted nuts); texture 3.08 (slightly springy); and overall preference is 3.24 (somewhat like). Keywords: analogue meatball, textured vegetable protein, green bean flour.